B4C-based hard and tough ceramics densified via spark plasma sintering using a novel Mg2Si sintering aid. Issue 1 (1st January 2023) - Zhang, Wenwen; Cao, Xichao; Zhang, Jinyong; Zou, Ji; Wang, Weimin; He, Qianglong; Ren, Lin; Zhang, Fan; Fu, Zhengyi
Abstract: Full-dense B4 C-based ceramics with excellent mechanical properties were fabricated using spark plasma sintering with Mg2 Si as a sintering aid at a low temperature of 1675 °C while applying a uniaxial pressure of 50 MPa. The effect of Mg2 Si addition on the densification behaviours, mechanical properties and microstructure of as-sintered ceramics were investigated. Not only did the formation of ultra-fine grained SiC using the in-situ reaction effectively inhibit the growth of B4 C grains, but it also contributed to the strength and toughness of the resultant ceramics. Additionally, microalloying Mg imparted more metal bonding characteristics to the B4 C matrix, thereby improving their ductility. The results indicate that the composite containing 7 wt% Mg2 Si had excellent mechanical properties, including a light weight of 2.54 g/cm 3, Vickers hardness of 34.3 GPa, fracture toughness of 5.09 MPa m 1/2 and flexural strength of 574 MPa.